Językoznawcze ujęcie problemu polskiej tożsamości narodowej w czasopiśmie "Polityka" = Polish Language Approach of the Problem of Polish National Identity in the Journal "Polityka" - Kaczor, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this paper is to attempt to explore the thinking of identity in contemporary Polish press, resulting from an analysis of linguistic facts. In the collected material to describe the lexical-semantic concept of Polish national identity it is taken into account its presence in syntagmatic contexts, and thus in a certain syntactic structure, in the context of the paradigm, that is, in the relation to the words associated with a given word.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie